Surgeon Profile: Peter Kalu: Contemporary Spotlights - McVeigh, Jamie (Journal of the Nuffield Department of Surgical Sciences, 2020)
Peter Kalu, Consultant Plastic & Reconstructive Surgeon at Oxford University Hospitals NHS Foundation Trust, discusses the importance of a measured approach to training and his key role in organising the national virtual Summit ‘Unlocking the NHS’ to collaborate strategies to improve healthcare during the Covid-19 pandemic.